Properties of thermally oxidized and nitrided Zr-oxynitride thin film on 4H–SiC in diluted N2O ambient - Wong, Y.H.; Cheong, K.Y. (Elsevier, 2012)
A systematic investigation on the structural, chemical, and electrical properties of thermally oxidized and nitrided sputtered Zr thin film in various N2O ambient (10–100%) at 500 °C for 15 min to form Zr-oxynitride on 4H–SiC substrate has been carried out. The chemical composition, depth profile analysis, and energy band alignment have been evaluated by X-ray photoelectron spectrometer. Zr-oxynitride layer and its interfacial layer comprised of compounds related to Zr–O, Zr–N, Zr–O–N, Si–N, and/or C–N were identified. A model related to the oxidation and nitridation mechanism has been suggested. Supportive results related to the model were obtained by energy filtered transmission electron microscopy, X-ray diffraction, and Raman analyses. A proposed crystal structure was employed to elucidate the surface roughness and topographies of the samples, which were characterized by atomic force microscopy. The electrical results revealed that 10% N2O sample has possessed the highest breakdown field and reliability. This was owing to the confinement of nitrogen-related compounds of Zr–O–N and/or Zr–N at or near interfacial layer region, smaller grain with finer structure on the surface, the lowest interface trap density, total interface trap density, and effective oxide charge, and highest barrier height between conduction band edge of oxide and semiconductor.